NUCLEAR RENAISSANCE AS A VIABLE SOLUTION FOR REDUCING GREENHOUSE GASES – THE ENVIRONMENTAL IMPACT OF DIFFERENT ENERGY TECHNOLOGIES - Žagar, Tomaž; Bergant, Robert; Fürst, Samo (Journal of Energy Technology, 2024)
Climate change is happening and represents one of the greatest environmental, social and economic threats facing the planet. The Intergovernmental Panel on Climate Change (IPCC), anassociation of scientists from all over the world, came to the conclusion that the main reason is the enhanced greenhouse effect. The production of electricity is, beside transportation, the most harmful contributor to the enhanced greenhouse effect. Unfortunately, the majority of electricity production is still based on a combustion of fossil fuels, e.g. coal, oil and gas. Renewable sources such as hydro, solar or wind are becoming increasingly preferable. Nuclear energy is also an important lowͲcarbon energy source with insignificant impact on the environment. Its whole cycle emissions are at least as low as the emissions of aboveͲmentioned renewable sources. Besides its environmental benefits, nuclear energy has also economical, spatial and social advantages over some other renewable sources. The purpose of the article is to present integrated environmental impacts for different technology chains used for electricity production. Two separate and independent studies are shown in this intention. A summary of different studies, made by Organization for Economic Cooperation and Development (OECD), presents the comparison of environmental impacts of different technology chains for the electricity production sector, based on data supplied by the OECD organization’s members. The study of the company GEN energija is focused on the comparison of environmental impacts of different technology chains that are feasible for electricity production in Slovenia, i.e. technologies such as nuclear, coal, gas, different renewable sources and a mixture of renewable sources, which include the hydro, biomass, wind and photovoltaic production. The evaluation of the environmental impacts for different energy technologies is implemented within radius 10 km of the existing location of Nuklearna elektrarna Krško (NEK) site, in order to evaluate and present the environmental consequences of different electrical power producing energy technologies. Electrical power production from four potential nuclear reactor designs, imported coalͲfired power generation, combinedͲcycle gasͲfired generation, and renewable power generation sources, including hydroelectric generation, solar photovoltaic generation, wind generation, biomass cogeneration, and geothermal electric generation are considered.Two assumptions for electrical power producing technologies are an installed capacity of 1,100 MWe and a 90% Baseload Capacity Factor. The renewable sources are evaluated as a resource mix (RES Mix) and are not capable reaching the required 90% Baseload Capacity Factor. It is assumed to have a combined 34% Baseload Capacity Factor if the evaluation region is expanded to the whole of Slovenia. For the RES Mix, 32% hydroelectric generation, 36% wind generation, 32% biomass cogeneration,